The quadruplex TaqMan MGB fluorescent quantitative PCR method for simultaneous detection of feline panleukopenia virus, feline herpesvirus 1, feline calicivirus and feline infectious peritonitis virus - Wang, Haojie; Xue, Lihong; Wang, Longxi; Liu, Yixuan; Chen, Jianxing; Sun, Yue; An, Tongqing; Chen, Hongyan; Yu, Changqing; Xia, Changyou; Zhang, He (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundFeline panleukopenia, feline calicivirus infection, feline viral rhinotracheitis, and feline infectious peritonitis are significant diseases that threaten feline health. The trend of mixed infections is increasing, and current diagnostic methods are limited in scope and unable to provide rapid, simultaneous detection of these diseases.MethodsFour groups of primers and probes targeting the VP2 gene of Feline Panleukopenia virus (FPV), the TK gene of Feline Herpesvirus (FHV-1), the ORF2 gene of Feline Calicivirus (FCV), and the N gene of Feline Infectious Peritonitis Virus (FIPV) were designed. After optimizing the concentrations of primers and probes and annealing temperature, a quadruplex TaqMan MGB fluorescent quantitative PCR method was established to concurrently detect these four pathogens. Recombinant plasmid standards were constructed to establish standard curves, and the sensitivity, specificity, reproducibility, and clinical application of the assay were evaluated.ResultsThe optimal final concentrations of primers for FPV, FHV-1, FCV, and FIPV were 0.08, 0.04, 0.06, and 0.12 μM, respectively, and the optimal final concentrations of probes were 0.08, 0.08, 0.12, and 0.12 μM, respectively. The best annealing temperature was 59°C. No cross-reaction was observed with common pathogens in infected cats. The minimal detection limits for recombinant plasmids of T-VP2, T-TK, T-ORF2, and T-N were 50.79, 53.21, 47.91 and 41.25 copies/μL, respectively. The R² values of standard curves are 0.994, 1.0, 0.998 and 0.999, respectively, and high amplification efficiencies of 105.05%, 96.28%, 98.82%, and 96.45%, respectively. The coefficient of variation for inter-batch and intra-batch tests ranged from 0.14 to 1.37%. Among 381 fecal samples from cats, the detection rates for FPV, FHV-1, FCV, and FIPV were 13.65% (52/381), 18.37% (70/381), 26.77% (102/381), and 9.71% (37/381), respectively, with a 100% agreement with previously reported methods and commercial kits.ConclusionThe sensitive, specific, high-throughput, quadruplex TaqMan MGB quantitative fluorescent quantitative PCR method was successfully established for the simultaneous detection of FPV, FHV-1, FCV, and FIPV.